Trends in the timber export trade in Ghana. A case study for Forestry Commission in Ghana - Nyan, Francis Ato (2016)
A thesis submitted to the Department of Mathematics,Institute of Distance Learning Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Science in Industrial Mathematics.